Circadian Pharmacological Effects of Paeoniflorin on Mice With Urticaria-like Lesions - Peng, Li; Wen, Lijuan; Zhang, Jie; Zhang, Xiaotong; Wei, Qin; Guo, Jing; Zeng, Jinhao (Frontiers in Pharmacology, 2022)
Paeoniflorin (PF) is a monoterpene glucoside with various biological properties, and it suppresses allergic and inflammatory responses in a rat model of urticaria-like lesions (UL). In the present study, we treated OVA-induced mice presenting UL with PF at four circadian time points (ZT22, ZT04, ZT10, and ZT16) to determine the optimal administration time of PF. The pharmacological effects of PF were assessed by analyzing the scratching behavior; histopathological features; allergic responses such as immunoglobulin E (IgE), leukotriene B4 (LTB4), and histamine (HIS) release; inflammatory cell infiltration [mast cell tryptase (MCT) and eosinophil protein X (EPX)]; and mRNA levels of inflammatory cytokines such as interleukin (IL)-12, IL-6, interferon-γ (IFN-γ), and IL-4. It was demonstrated that PF significantly alleviated scratching behavior and histopathological features, and ZT10 dosing was the most effective time point in remission of the condition among the four circadian time points. Moreover, PF decreased the serum levels of IgE, LTB4, and HIS, and PF administration at ZT10 produced relatively superior effectiveness. PF treatment, especially dosing at ZT10, significantly reduced the number of mast cells and granules and diminished the infiltration of MCT and EPX in the skin tissues of mice with UL. Furthermore, the oral administration of PF effectively decreased the inflammatory cytokine levels of IL-12 mRNA. In conclusion, different administration times of PF affected its efficacy in mice with UL. ZT10 administration demonstrated relatively superior effectiveness, and it might be the optimal administration time for the treatment of urticaria.